RELATIONSHIP OF METACOGNITIVE AWARENESS AND SELF EFFICACY TO MATHEMATICS LEARNING OUTCOMES - Vita Sari, Enie; Sumilah, Sumilah (Universitas Negeri Semarang, 2019)
This research aimed to examine the correlation between metacognitive awareness and self efficacy to the Mathematics learning outcomes of 4 th grade students in elementary school Cluster Cakra Semarang. This research used a quantitative study with the type of correlation research. The population of this study amounted to 288 students. Sampling with cluster sampling obtained 167 students. The data collection technique used questionnaire. The data analysis techniques used descriptive statistics and correlation analysis. The results showed positive and significant relationship between metacognitive awareness and self efficacy towards Mathematics learning outcomes. The percentage of correlation was 73.96%. The r coefesient value showed 0.860 and the significance value showed 0.05. In conclusion, there was a positive and significant correlation between metacognitive awareness and self efficacy to the learning outcomes Mathematics learning outcomes of 4 th grade students in elementary school Cluster Cakra Semarang.